Efficiency Determinants of Zakat Institutions in Indonesia - Nashr Akbar; Ihsanul Ikhwan; Novan Nurpahla (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
ABSTRACT - The purpose of this study is to examine the relative efficiency of national zakat organizations in Indonesia. Data was collected from decision-making units (DMU) consisting of 14 national zakat institutions in Indonesia listed on the BAZNAS website and selected using the purposive sampling technique. The information was derived from the DMU's publicly accessible financial reports. This study utilized the Data Envelopment Analysis (DEA) output-oriented approach to maximize output with the same level of input when analyzing the data. In selecting input variables, this study consulted previous research. In addition, it utilized Tobit regression based on the outcome of Maximum Likelihood (ML) to evaluate the determinants of the efficiency value (dependent variable) as the score ranges from 0 to 100. The result indicates that the efficiency of zakat institutions fluctuates slightly throughout the observation period. In addition, the significant efficiency determinants are size and community membership. Therefore, zakat organizations must maintain and increase their donors' loyalty. It is anticipated that the findings will contribute to the advancement of practice and knowledge regarding the study of zakat literature.   ====================================================================================================ABSTRAK – Determinan Efisiensi Lembaga Zakat di Indonesia. Penelitian ini bertujuan untuk mengkaji tingkat efisiensi relatif instituti zakat di Indonesia. Data dikumpulkan dari unit pengambil keputusan yang terdiri 14 lembaga zakat nasional yang terdaftar pada situs BAZNAS dan dipilih dengan teknik sampel purposif. Informasi yang diolah berasal dari laporan keuangan yang dapat diakses secara publik. Analisis data menggunakan Data Envelopment Anaysis (DEA) dengan pendekatan output-oriented yang memaksimalkan output di level yang sama dengan tingkat input. Dalam memilih variabel input, kajian ini menggunakan beberapa hasil riset sebelumnya. Selanjutnya, analisis data juga dilakukan dengan Tobit regression yang mendasarkan pada outcome dari Maximum Likelihood (ML) dengan maksud untuk mengevaluasi determinan nilai efisensi dalam rentang skor 0 sampai 100. Temuan kajian ini mengindikasikan bahwa tingkat efisiensi lembaga zakat di Indonesia cenderung berfluktuasi dalam periode yang diamati. Selain itu, determinan yang berpengaruh signifikan terhadap pencapaian tingkat efisiensi adalah ukuran (asset) dan afiliasi terhadap komunitas. Oleh karena itu, lembaga zakat harus menjaga dan meningkatkan loyalitas para donaturnya. Hasil kajian ini dapat berkontribusi pada kemajuan pengelolaan zakat dan memperkaya khazanah pengetahuan zakat dalam literatur.